Physiology in Modelica - Mateják, Marek (Mefanet journal, 2014)
Modelica is an object-oriented language, in which models can be created and graphically represented by connecting instances of classes from libraries. These connections are not only assignments of values; they can also represent acausal equality. Even more, they can model Kirchhoff's laws of circuits. In Modelica it is possible to develop library classes which are an analogy of electrical circuit components. The result of our work in this field is Physiolibrary (www.physiolibrary.org) – a free, open-source Modelica library for human physiology. By graphical joining instances of Physiolibrary classes, user can create models of cardiovascular circulation, thermoregulation, metabolic processes, nutrient distribution, gas transport, electrolyte regulation, water distribution, hormonal regulation and pharmacological regulation. After simple setting of the parameters, the models are ready to simulate. After simulation, the user can examine variables as their values change over time. Representing the model as a diagram has also great educational advantages, because students are able to better understand physical principles when they see them modeled graphically.
Keywords: Computer Simulation; biologické modely; Computer Graphics; Physiology; lidé; fyziologie; Models, Biological; počítačová grafika; počítačová simulace; Humans